2009
DOI: 10.1002/syn.20637
|View full text |Cite
|
Sign up to set email alerts
|

Reported childhood abuse is associated with low serotonin transporter binding in vivo in major depressive disorder

Abstract: Background Physical or psychological adversity in childhood is associated with a higher risk for depression in adulthood, and with persistent serotonergic abnormalities in humans and in animal models. We hypothesized that reported childhood abuse would be associated with lower brain serotonin transporter (5-HTT) binding potential (BPP, proportional to the number of available transporters) in adults. We examined healthy volunteers and subjects with major depressive disorder, a sample enriched for childhood abus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 67 publications
7
61
1
1
Order By: Relevance
“…Although recent methodological developments have permitted the use of experimental animals for in vivo brain imaging, few studies have examined the behavioral personality traits of nonhuman primates (Morgan et al 2002;Heinz et al 2003;Ichise et al 2006). Using a specific tracer for SERT, PET studies with macaque monkeys have revealed that regional abnormalities in brain serotonergic systems may be related to behavioral abnormalities caused by early life stress Wrase et al 2006), which is similar to that observed in a human PET study (Miller et al 2009). PET imaging studies with human and nonhuman primates have thus acted as a bridge between basic and clinical research.…”
Section: Nonhuman Primate Studiesmentioning
confidence: 82%
See 1 more Smart Citation
“…Although recent methodological developments have permitted the use of experimental animals for in vivo brain imaging, few studies have examined the behavioral personality traits of nonhuman primates (Morgan et al 2002;Heinz et al 2003;Ichise et al 2006). Using a specific tracer for SERT, PET studies with macaque monkeys have revealed that regional abnormalities in brain serotonergic systems may be related to behavioral abnormalities caused by early life stress Wrase et al 2006), which is similar to that observed in a human PET study (Miller et al 2009). PET imaging studies with human and nonhuman primates have thus acted as a bridge between basic and clinical research.…”
Section: Nonhuman Primate Studiesmentioning
confidence: 82%
“…Similarly, the effects of childhood adversity on SERT binding were confirmed in a human PET study using patients with major depression (Miller et al 2009). …”
Section: Serotonin Transportersmentioning
confidence: 87%
“…Moreover, there are several aspects other than genetic ones that have been shown to influence or associate with serotonin transporter binding. These include ethnicity (Praschak-Rieder et al, 2007), personality (Kalbitzer et al, 2009), biography (Miller et al, 2009) and psychiatric diagnoses (Malison et al, 1998;Meyer et al, 2004;Selvaraj et al, 2009; for review see Meyer, 2007;Stockmeier, 2003), and, as recently shown, time of the year when scanning takes place. Using [ 11 C]DASB and PET, we were able to show that serotonin transporter binding varies across seasons, with highest binding measured in fall and winter, and lower binding measured in spring and summer, with peak differences being as high as 40% (Praschak-Rieder et al, 2008).…”
Section: Serotonin Transporter Gene Linked Polymorphic Region (5-httlpr)mentioning
confidence: 97%
“…For example, a common triallelic polymorphism at the serotonin transporter-linked polymorphic region (5-HTTLPR) on chromosome 17q12 impacts on SERT mRNA transcription and confers variability in SERT expression that is measurable by 11 C-DASB PET (Praschak-Rieder et al, 2007;Reimold et al, 2007). Environmental factors include seasonal variation in SERT availability (Praschak-Rieder et al, 2008) and evidence that childhood adversity may be associated with a persisting reduction of SERT availability in adulthood (Miller et al, 2009). A recent PET study has found low SERT to be associated with poor treatment response to other drugs (antidepressants) acting largely via monoamine reuptake inhibition (Miller et al, 2008).…”
Section: Discussionmentioning
confidence: 99%